Idiosyncratic Biogenesis of Intracellular Pathogens-Containing Vacuoles - Vaughn, Bethany; Abu Kwaik, Yousef (Frontiers in Cellular and Infection Microbiology, 2021)
While most bacterial species taken up by macrophages are degraded through processing of the bacteria-containing vacuole through the endosomal-lysosomal degradation pathway, intravacuolar pathogens have evolved to evade degradation through the endosomal-lysosomal pathway. All intra-vacuolar pathogens possess specialized secretion systems (T3SS-T7SS) that inject effector proteins into the host cell cytosol to modulate myriad of host cell processes, and remodel their vacuoles into proliferative niches. Although intravacuolar pathogens utilize similar secretion systems to interfere with their vacuole biogenesis, each pathogen has evolved with a unique toolbox of protein effectors injected into the host cell to interact with, and modulate, distinct host cell targets. Thus, intravacuolar pathogens have evolved with clear idiosyncrasies in their interference with their vacuole biogenesis to generate a unique intravacuolar niche suitable for their own proliferation. While there has been a quantum leap in our knowledge of modulation of phagosome biogenesis by intravacuolar pathogens, the detailed biochemical and cellular processes affected remain to be deciphered. Here we discuss how the intravacuolar bacterial pathogens Salmonella, Chlamydia, Mycobacteria, Legionella, Brucella, Coxiella, and Anaplasma utilize their unique set of effectors injected into the host cell to interfere with endocytic, exocytic, and ER-to-Golgi vesicle traffic. However, Coxiella is the main exception for a bacterial pathogen that proliferates within the hydrolytic lysosomal compartment, but its T4SS is essential for adaptation and proliferation within the lysosomal-like vacuole.